Analisis implementasi matriks Leslie pada model laju pertumbuhan populasi perempuan - Musyarofah, Siti; Sofhya, Herlinda Nur’afwa (Perspectives in Mathematics and Applications, 2025)
Demographic problems in Indonesia are important because Indonesia is ranked fourth as the country with the largest population. One way to determine future population growth is to predict female population growth. The Leslie matrix is a model used to predict and determine female population growth. The general form of the Leslie matrix is a square matrix in which the first row entries are the female fertility rates, the subdiagonal entries are the female survival rates, and the remaining entries are zero. The purpose of the study was to predict the rate of female population growth in Indonesia. The results showed that the Leslie matrix, influenced by the initial population, female fertility rate, and female survival rate, had a dominant eigenvalue of 1.001, indicating that the rate of female population growth in Indonesia tends to increase.